2022
DOI: 10.1186/s12985-022-01957-1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive immune responses and cytokine immune profiles in humans following prime and boost vaccination with the SARS-CoV-2 CoronaVac vaccine

Abstract: Background Adaptive immune response has been thought to play a key role in SARS-CoV-2 infection. The role of B cells, CD4+T, and CD8+T cells are different in vaccine-induced immune response, thus it is imperative to explore the functions and kinetics of adaptive immune response. We collected blood samples from unvaccinated and vaccinated individuals. To assess the mechanisms contributing to protective immunity of CoronaVac vaccines, we mapped the kinetics and durability of humoral and cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Moreover, the development of natural killer cells, dendritic cells, and macrophages was also predicted to sustain growth after each immunization ( Figures 9F–H ). Vaccine dosages are commonly reported to stimulate the release of a variety of cytokines, including IFN-gamma, IL-23 (interleukin-23), IL-10, and IFN-beta, that eventually promote an immune response against infection ( 65 , 66 ). In the case of the proposed construct-IV, significantly elevated levels of cytokines and interleukins, including IFN-γ and TGF-B, were predicted after continuous antigen exposure during immunization periods, while the other cytokines present lower concentration detection ( Figure 9I ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the development of natural killer cells, dendritic cells, and macrophages was also predicted to sustain growth after each immunization ( Figures 9F–H ). Vaccine dosages are commonly reported to stimulate the release of a variety of cytokines, including IFN-gamma, IL-23 (interleukin-23), IL-10, and IFN-beta, that eventually promote an immune response against infection ( 65 , 66 ). In the case of the proposed construct-IV, significantly elevated levels of cytokines and interleukins, including IFN-γ and TGF-B, were predicted after continuous antigen exposure during immunization periods, while the other cytokines present lower concentration detection ( Figure 9I ).…”
Section: Resultsmentioning
confidence: 99%
“…Statins and metformin have been reported to impair the antibody response and efficacy of vaccines [ 59 , 60 ], and information on these administrations was also lacking. Previous research identified CD4 + T cells as the hallmark of a vaccine-induced SARS-CoV-2–specific T cell response [ 61 , 62 ], in particular TNF-α and IL-2 producing CD4 + T cells [ 63 ]. Therefore, in addition to analyzing humoral responses, an evaluation of T cell responses in these immunosuppressed patients would have been crucial for better understanding the immunological responses to vaccination and previous infections; however, our study design precluded this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, it might be more evident in vaccines that activate the immune system as their primary mechanism. A rise in the number of these cytokines has been observed post-vaccination when using such vaccines as influenza and COVID-19 and might be more evident in subjects who have already had contact with either virus or their first dose of a vaccine [27,28]. With the ongoing high COVID-19 transmission in 2022, it was difficult to evaluate individuals' exposure [29].…”
Section: Discussionmentioning
confidence: 99%